Comparison of Effect of Two Treatment Methods: Oxygen Therapy with Face Mask and Nasal Catheter on Nausea and Vomiting and Comfort in Cesarean section under Spinal Anesthesia - Ainaz Kor; Khadijeh Yazdi; Hosien Nasiri; Mohsen Mir Sadeghi (Golestan University of Medical Sciences, 2017)
Background: Receiving Oxygen during Cesarean section under spinal anesthesia can be a good way to prevent from nausea and vomiting of mothers and hypoxemia of fetus. This study aimed to compare the effect of two treatment methods of Oxygen therapy with facemask and nasal catheter on vomiting and nausea and patient's comfort during Cesarean section under spinal anesthesia. Methods: This clinical trial study was conducted  on 50 candidate patients for elective cesarean section, recruited via convenience sampling , were divided into two groups. For the first group, 8 liters of Oxygen per minute with face mask and for the second one, 4 liters of Oxygen per minute with nasal catheter was administered during cesarean section and after that in recovery unit. Nausea, vomiting and comfort were recorded during the first 30 min of surgery and in recovery unit. Data were analyzed by Mann-Whitney test, independent t test, Fisher's exact test and Chi-square tests.  Results: No significant difference was observed between two groups in terms of nausea and vomiting during surgery and after that.  Moreover, there was no significant difference between two groups in terms of comfort during (p=0.14) and after surgery (p=0.12).  In terms of clinical treatment, patients who received Oxygen through nasal catheter felt more comfort. Conclusion: Nasal catheter by administering lower dose of oxygen had a similar effect to face mask on nausea and vomiting. Therefore, since patients feel more comfort when using nasal catheter, it is preferable in preventing the nausea and vomiting in Cesarean section during spinal anesthesia.